Consequences of unintended pregnancy among young married women in Nepal - Puri, Mahesh (Nepal Journal of Obstetrics and Gynaecology, 2009)
Aim: To explore the consequence of unintended pregnancy, and compare these with real experiences amongst young married women in Nepal. Method: Sample survey of 997 married women and 19 in-depth case histories were studied. Results: The findings suggest that conflicts with spouses and family members, depression, worries or mental tension, loss of education and employment opportunities were the major anticipated socio-psychological consequences of unintended pregnancies. Reduced prenatal and postnatal care, unsafe abortions, postabortion complications, and maternal deaths were the major expected health outcomes of an unintended pregnancy. In general, the perceived opinions on socio-psychological consequences corroborated with real experiences. However, there are some differences between the perceived opinions and real experiences. Conclusions: Programmes that focus to identify couples at risk of unintended pregnancies, to address worries and mental tension, and enable them to make timely decisions and responsible choices are required. Keywords: abortions, health consequences, maternal deaths, socio-psychological consequences, unintended pregnancy doi:10.3126/njog.v1i2.2396 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 37-46 Nov-Dec 2006